Learning Outcomes of Virtual Journal Clubs in Comparison to Real Ones in Pediatric Neurology Fellows - Mohammadi, Mahmoud; Zolfaghari, Mitra; Shervin Badv, Reza; Javadzadeh, Mohsen; Rezaei, Zahra; Ashrafi, Mahmoudreza; Heidari, Morteza; Zamani, Gholamreza; Pourbakhtyaran, Elham (Iranian Journal of Child Neurology, 2025)
Objectives: Journal Club sessions are a staple in clinical training, widely implemented across various specialities. This study aims to compare the effectiveness if in-person and virtual Journal Club sessions . Materials & Methods: This compartive study involved pediatric neurology residents from two institutions: six residents from Children's Medical Centerattended in-person sessions, while seven residents from Mofid Children's Hospital participated in virtual sessions. Evaluations were based on an interaction and behavior checklist during the sessions, apost-test consisting of ten multiple-choice questions, and a student-satisfaction questionnaire . Results: A total of 13 pediatricneurology residents(12 women and 1 man) participated. The average knowledge score was higher in virtual sessions compared to the in-person sessions, though this difference was not statistically significant. High satisfaction(score of 4) for active participation was reported by 50% of in-person attendees and 57.1% of virtual attendees, with nosignificant difference. For analytic assessment of statistical tests in articles, high satisfaction was reported by 83.3% of in-person attendees and 100% of virtual attendees, also not significantly different . Conclusion: The findings suggest that virtual Journal Clubs can be effective and satisfactory as in-person sessions. Further studies with larger sample sizes are recommended to validate these results.